(untitled) (Medico Legal Update, 2019)
Objectives: This study was designed to identify the factors affecting nurses’ implementation of evidence-based fall guidelines in long-term care hospitals. Method: Using a descriptive study design, the participants were 217nurses from long-term care hospitals in Korea. The data were used descriptive analysis, correlation, and multiple regression. The survey was designed to investigate nurses’ EBP beliefs, EBP organizational culture, EBP implementation regarding implementation of evidence-based fall guidelines. Findings: EBP beliefs (? = .23, p < .001), EBP organizational culture (? = .49, p < .001), and EBP implementation (? = .15, p = .025) were significant predictors which explained 57.6% of the variance reported in implementation of evidence-based fall guidelines. Improvements/Applications: The results of this study support the need for nursing organizations to create cultures that promote EBP and to encourage nurses’ beliefs about their confidence and capability to implement upon implementation of evidence-based fall guidelines. This could enhance patient care and outcomes, as well as organizational outcomes.